Amiodarone/N‐desethylamiodarone population pharmacokinetics in paediatric patients. Issue 12 (29th July 2022) - Lehnert, Amélia; Foissac, Frantz; Bouazza, Naïm; Urien, Saïk; Oualha, Mehdi; Renolleau, Sylvain; Barbanti, Claudio; Di Marzio, Anna; Bonnet, Damien; Abdalla, Seef; Zheng, Yi; Treluyer, Jean‐Marc
Abstract : The population pharmacokinetics of amiodarone and its active metabolite, N‐desethylamiodarone (DEA) were investigated in paediatric patients with arrhythmias, mainly supraventricular tachycardias. A total of 55 patients from the Department of Pediatric Intensive Care and Pediatric Cardiology at Necker‐Enfants malades Hospital (Paris, France) provided 72 concentrations for both amiodarone and DEA following repeated oral or intravenous administration. Blood samples drawn for biological analyses were used for drug concentrations. Plasma amiodarone concentrations were measured by a liquid chromatography method coupled with mass spectrometry and the data were modelled using the software Monolix 2019R2. Parent pharmacokinetics was described with a 2‐compartment open model and the metabolite formation was connected to the central parent compartment. Parameter estimates scaled allometrically on bodyweight (normalized to 70 kg) were, respectively (% relative standard errors, RSEs), 6.32 (31%) and 7.14 L/h (26%) for elimination (CL) and intercompartmental clearances and 167 (31%) and 3930 (32%) L for V1 and V2 . Oral bioavailability was 0.362 (21.5%). The clearance between subject variability (ω, square root of the variance) was 0.462 (RSE 21%). The proportional residual variabilities were respectively 0.453 (RSE 13%) and 0.423 (RSE 12%) for amiodarone and DEA respectively. The terminal half‐lives were 34 and 14.5 days for amiodarone and DEA, respectively. A dosage schedule was established for 3 weight bands in 2 time periods. The high pharmacokinetic variability suggests that therapeutic drug monitoring might be useful to improve individual efficacy and safety.